Prime Minister Decree No. 1820/2015 Promulgating The Executive Regulation Of Investment Guarantees And Incentives Law = قرار رئيس مجلس الوزراء رقم 1820 لسنة 2015 بإصدار اللائحة التنفيذية لقانون ضمانات وحوافز الاستثمار - Egypt; The middle east library for economic services, translator. (2025)
81, 50 pages ;